Influência dos cimentos biocerâmicos Biodentine e Bio C Repair nas respostas de macrófagos M1 e M2 de murinos - Marcela Martins Costa (2020)
Bioceramic cements can be used in endodontics as repair materials and have additional properties in relation to the first bioceramic, MTA, such as better flow and handling. This work aimed to evaluate the effect of bioceramic cements: Biodentine (Septodont, Saint-Maur-desFossés, France), Bio-C Repair (Angelus, Londrina, Paraná, Brazil) and MTA (Angelus, Londrina, Paraná, Brazil) - used as the gold standard - in the responses of murine M1 and M2 macrophages regarding cell viability, adherence capacity, phagocytosis and production of reactive oxygen species. The research was submitted to the Ethics and Research Committee on Animals (CEUA UFMG) and was carried out in the laboratory of Gnotobiology and Immunology of the Institute of Biological Sciences (ICB) of the Federal University of Minas Gerais. Two strains of mice were used: C57BL / 6, for recovery of peritoneal macrophages M1, and BALB / c, for recovery of peritoneal macrophages M2. The data were analyzed using the ANOVA test (p <0.05). There was less cell viability compared to control in the 24- hour cultures of M1 and M2 macrophages treated with Biodentine (p <0.05), using MTT methods and trypan blue exclusion. In 72h, all cements showed significant difference in relation to the control (p <0.05), in the cultures of M1 cells, regarding cell viability, analyzed by the trypan blue method. There was no significant difference (p> 0.05) in cell adhesion between the two types of macrophages treated by the different cements. It was observed in the phagocytosis assay that M1 macrophages had a higher mean number of intracellular yeasts than M2 macrophages (p <0.05). Regarding the production of reactive oxygen species, M1 macrophages treated with Biodentine induced greater production when compared to other cements, in the presence of zymosan A. (p <0.05). When comparing the production of reactive oxygen species (ROS) between the two types of macrophages, a greater production by M1 cells was observed (p <0.05). It was concluded that the repairing bioceramic materials presented similar responses to MTA, emphasizing the excellent biocompatibility of Biodentine and Bio-C Repair cements.